MANAGING DISSENT, LIMITING RISK AND CONSOLIDATING POWER: THE PROCESSES AND RESULTS OF CONSTITUTIONAL REFORM IN KAZAKHSTAN - ISAACS, Rico (CENTRAL ASIA AND THE CAUCASUS, 2008)
The transition in much of the former Soviet Union has not led to democracy but instead to varying degrees of authoritarianism and dictatorship.1 Yet some states driven by endogenous and exogenous factors are pursuing a proc-ess of constitutional reform for the purpose of democratizing political processes. In the cases of Ukraine and Kyrgyzstan, among other factors, the process has been driven by the emergence of a “counter elite” that has provided an effective challenge to the incumbent power. The constitutional reform process in both Ukraine and Kyrgyzstan has been characterized by elite conflict, civic pro-test and the paralysis of government in both the executive and legislative branches. In Kazakhstan President Nursultan Nazarbaev believes his country is pursuing a unique model of constitutional and political reform that is defined by a moderate step-by-step process. Unlike the crises that have enveloped the process in Ukraine and Kyrgyzstan, the Kazakh model places economic stability be-fore political reform and posits gradual democratization over radical change.2 Whereas in Ukraine and Kyrgyzstan a counter elite emerged,Nazarbaev has been able to define the political rules of the game on his own terms by disabling the ability of competing elite and opposition groups to compete for power. However, the Kazakh specific model of political modernization does not exist in a vacuum as internal and external factors are driving the process. Externally, approval from the international community has been a driving factor; in particular, the bid for chairmanship of the OSCE in 2009 has added a sense of urgency to complete the process. Internally, the emergence of an economic counter elite, the nontransparent electoral process and conflicts between competing elite groups, were all factors contributing toward the initiation and continuation of the reform process. On 16 May, 2007, the president announced to a joint session of parliament changes to the constitution that were to signal, in particular to the West, that Kazakhstan is finally moving to reform its authoritarian political system. In the West some analysts and political representatives responded positively to the amendments.3 The administration is arguing the reforms constitute a shift to a presidential-parliamentary system. In this context, the aim of this paper is to survey the process and results of constitutional reform in Kazakhstan. It seeks explore and address two questions: what were the factors influencing the process of reform? And what do the results of the process tell us about the nature of Kazakhstan’s political transition. In answering these questions the article will examine the three bodies4 created by the president that have been used as a conduit for developing a dialog between the authorities,political parties and wider civil society, thus ex-ploring the interconnection between the endog-enous and exogenous variables affecting the proc-ess. The article will also analyze the results of the process in the form of the constitutional amend-ments. In analyzing the activities and role of the three bodies designated as enablers of political reform, the factors driving the process, and the output of the process, this article will argue that the changes were formulated by the presidential administration as an attempt to balance the com-peting demands of internal and external pressures.his is reflected in a need by the president to manage dissent within the country, while at the same time promoting Kazakhstan’s specific model of political modernization to the international community. However, the results of the process, which has seen the marginalization of opposition voices, suggest the president is limiting the possibility of any form of risk that challenges his position, while at the same time trying to present to the West the democratization of Kazakhstan.therefore, the reforms amount not to a shift to-ward a presidential-parliamentary system, but instead a further consolidation of presidential power.